(untitled) (Fiep Bulletin - online, 2016)
The participation of people with disabilities in physical activity programs has been encouraged, however, there are difficulties to develop therapeutic strategies that can respect their differences. Some features can be used as health professionals working tools highlighting the video game. The aim of this study was to perform a systematic review on the use of video games as a therapeutic practice (gameterapy) for people with disabilities. The databases used were the National Center for Biotechnology Information (PubMed) and Scientific Electronic Library Online (SciELO). The keywords used for the search were: virtual reality; disabled persons; wii and their combinations. There were included in the search studies published between 2012-2015, full papers, with application of gameterapia as intervention in people with disabilities. From the above criteria, there were six articles included in this study for detailed analysis. In these studies the variables were: motor coordination, agility , displacement and weight bearing, postural adjustments, balance and muscle strength in the legs. From the results obtained it can be concluded that the use of gameterapia significantly improved development and physical capacity people with disabilities. Importantly, the search area is relatively new, so the consistency of the evidence is not so strong, with low scientific content studies with small number or case reports.